Non-invasive Technology Advances in Cancer—A Review of the Advances in the Liquid Biopsy for Endometrial and Ovarian Cancers - Openshaw, Mark R.; McVeigh, Terri P. (Frontiers in Digital Health, 2020)
Improving cancer survival rates globally requires improvements in disease detection and monitoring, with the aim of improving early diagnosis and prediction of disease relapse. Traditional means of detecting and monitoring cancers rely largely on imaging and, where possible, blood-based protein biomarkers, many of which are non-specific. Treatments are being improved by identification of inherited and acquired genomic aberrations in tumours, some of which can be targeted by newly developed therapeutic interventions. Treatment of gynaecological malignancy is progressively moving towards personalised therapy, as exemplified by application of PARP-inhibition for patients with BRCA-deficient tubo-ovarian cancers, or checkpoint inhibition in patients with mismatch repair-deficient disease. However, the more recent discovery of a group of biomarkers described under the umbrella term of ‘liquid biopsy’ promises significant improvement in our ability to detect and monitor cancers. The term ‘liquid biopsy’ is used to describe an array of tumour-derived material found in blood plasma and other bodily fluids such as ascites, pleural fluid, saliva and urine. It includes circulating tumours cells (CTCs), circulating nucleic acids including DNA, messenger RNA and micro RNAs, and extracellular vesicles (EVs). In this review, we discuss recent advancements in liquid biopsy for biomarker detection to help in diagnosis, prognosis and planning of treatment of ovarian and endometrial cancer.